2020
DOI: 10.1186/s12916-020-01686-8
|View full text |Cite
|
Sign up to set email alerts
|

In utero and childhood exposure to tobacco smoke and multi-layer molecular signatures in children

Abstract: Background: The adverse health effects of early life exposure to tobacco smoking have been widely reported. In spite of this, the underlying molecular mechanisms of in utero and postnatal exposure to tobacco smoke are only partially understood. Here, we aimed to identify multi-layer molecular signatures associated with exposure to tobacco smoke in these two exposure windows. Methods: We investigated the associations of maternal smoking during pregnancy and childhood secondhand smoke (SHS) exposure with molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…Our results may indicate that the pregnancy period is most sensitive to the harmful effects of these exposures which is in line with the very rapid development of the nervous system during this time window but also the different ways individuals are exposed, for example in utero and/or passively to tobacco smoke ( Peterson et al, 2015 , Allen et al, 2017 ). In line with our results, childhood second-hand smoke (SHS) was not related to blood methylation in HELIX children (biomarkers of past exposure), indicating much weaker effects of recent SHS with respect to active maternal smoking in pregnancy ( Vives-Usano et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Our results may indicate that the pregnancy period is most sensitive to the harmful effects of these exposures which is in line with the very rapid development of the nervous system during this time window but also the different ways individuals are exposed, for example in utero and/or passively to tobacco smoke ( Peterson et al, 2015 , Allen et al, 2017 ). In line with our results, childhood second-hand smoke (SHS) was not related to blood methylation in HELIX children (biomarkers of past exposure), indicating much weaker effects of recent SHS with respect to active maternal smoking in pregnancy ( Vives-Usano et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…While blood DNA methylation and transcriptomics were measured genome-wide, the other omics followed a semi-targeted or targeted approach. Details of the plasma proteins and the urinary and serum metabolomic analyses can be found elsewhere (Lau et al, 2018; Vives-Usano et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we observed that child exposure to second-hand smoke (cluster childhood#7) overlapped with existing literature, but to a lesser extent than maternal smoking (Figure 5C; Table S3) . Period specific effects have been investigated elsewhere in more detail (Vives-Usano et al, 2020). In order to understand which pathways were perturbed due to exposure to tobacco smoke, we performed functional enrichment analysis of genes annotated to molecular features associated with pregnancy or childhood exposure (Supplemental Experimental Procedures) .…”
Section: Resultsmentioning
confidence: 99%
“…However, the top nominally significant CpG sites were found in the genes FRMD4A, MYO1G, WIPF3 , and RTN1 . CpG sites in genes MYO1G and FRMD4A have been previously found to be differentially methylated in response to maternal smoking during pregnancy [4042]. However, the CpG sites cg20745684 and cg01604380 within the genes WIPF3 and RTN1 respectively have not been implicated in any previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Myosin 1G ( MYO1G ) and FERM Domain Containing 4A ( FRMD4A ) are more established biomarkers for in utero tobacco exposure [4042]. However, these prior results come from the analysis of DNA methylation during childhood.…”
Section: Discussionmentioning
confidence: 99%